Best Answer

7x - 9y = 35

-3x + 6y = -15 (divide the second equation by 3, after that multiply it by 7)

7x - 9y = 35

-7x + 14y = -35 (add both equations)

5y = 0 (divide both sides by 5)

y = 0

7x - 9y = 35 (substitute 0 for y)

7x = 35 (divide both sides by 7)

x = 5

Thus the solution of the given system of the equations is x = 5 and y = 0.

Study guides

☆☆

Q: Solve the system by the elimination method 7x-9y equals 35 plus -3x plus 6yequals -15?

Write your answer...

Submit

Still have questions?

Related questions

By elimination: x = 3 and y = 0

Simultaneous equations can be solved using the elimination method.

Solve the system by the elimination method 5x 5y-13 7x-3y17what is the solution to the system?

Solving by elimination: p = 3 and q = -2

x + 4y = -14 eqn12x + 3y = 13 eqn2Using the elimination method we multiply eqn1 by 22x + 8y = -28 eqn1bSubtract eqn2 from eqn1b2x + 8y = -28 eqn1b2x + 3y = 13 eqn25y =-41y = -8 and 1/5substituting this into eqn1 we getx +4 (-41/5) = -14x = (14*5) / (41 *4)x = (35/82)

It is called solving by elimination.

A method for solving a system of linear equations; like terms in equations are added or subtracted together to eliminate all variables except one; The values of that variable is then used to find the values of other variables in the system. :)

2x + 2y = 44x + y = 1There are many methods you can use to solve this system of equations (graphing, elimination, substitution, matrices)...but no matter what method you use, you should get x = -1/3 and y = 7/3.

the answer

There is no simple answer. Sometimes, the nature of one of the equations lends itself to the substitution method but at other times, elimination is better. If they are non-linear equations, and there is an easy substitution then that is the best approach. With linear equations, using the inverse matrix is the fastest method.

One way to solve this system of equations is by using matrices. Form an augmented matrix in which the first 2x2 matrix is the coefficient matrix and the 2x1 matrix on its right is the answer. Now apply Gaussian Elimination and back-substitution. Using this method gives x=5 and y=1.

how do you use the substitution method for this problem 2x-3y=-2 4x+y=24

People also asked